2023
DOI: 10.1007/s13300-022-01363-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ramadan Fasting on Glycaemic Control Among Patients with Type 2 Diabetes: Systematic Review and Meta-analysis of Observational Studies

Abstract: Introduction:The prevalence of type 2 diabetes (T2D) is increasing around the world. Although Muslims with a physical illness are exempted from fasting during the month of Ramadan, a great number still choose to fast, often without medical consultations. The aim of this systematic review and meta-analysis was to investigate the impact of observing Ramadan fasting (RF) on glycaemic control in patients with T2D.Methods: The Web of Science, Scopus, EBSCOhost, CINAHL, ScienceDirect, Cochrane Library, ProQuest Cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Usually they eat two meals a day, one before the sunrise and the other shortly after sunset. Systematic reviews and meta-analyses have shown that Ramadan fasting promoted minimal improvements in fasting glucose in healthy subjects [ 6 ], although greater effects were found in subjects with type 2 diabetes [ 48 , 49 ]. There is a significant but small body weight loss after Ramadan practice [ 50 ], though this lost weight is rapidly regained [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Usually they eat two meals a day, one before the sunrise and the other shortly after sunset. Systematic reviews and meta-analyses have shown that Ramadan fasting promoted minimal improvements in fasting glucose in healthy subjects [ 6 ], although greater effects were found in subjects with type 2 diabetes [ 48 , 49 ]. There is a significant but small body weight loss after Ramadan practice [ 50 ], though this lost weight is rapidly regained [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Elmajnoun et al 13 performed a systematic review and meta-analysis to investigate the impact of RF on glycemic control in patients with T2D in relevant studies (January 2000–December 2021). Observational studies that examined the changes in BW and glucose parameters (HbA1c and FBG) before and after RF among different age groups with T2D were included in the systemic review and meta-analysis.…”
Section: Highlights Of the Literaturementioning
confidence: 99%
“…As a result, it has been observed that people observing a period of pre-Ramadan assessment with clinicians, as a personalized approach, could improve metabolic balance and also prevent acute complications during and after Ramadan period. 99,100 Nutrigenetics studies the role of genetic variants in the modulation of response to diet and the implications in the development, or prevention, of diseases. In particular, some genetic variants seem associated with diet response for what concerns the development of cardiovascular diseases, mainly obesity and diabetes.…”
Section: Dietmentioning
confidence: 99%